Daratumumab-based quadruplet versus triplet induction regimens in transplant-eligible newly diagnosed multiple myeloma: a systematic review and meta-analysis - Souto Filho, João Tadeu Damian; Cantadori, Lucas Oliveira [UNESP]; Crusoe, Edvan de Queiroz; Hungria, Vania; Maiolino, Angelo (Springer Nature, 2025)
The treatment landscape for transplant-eligible patients with newly diagnosed multiple myeloma (TE-NDMM) has evolved with the introduction of daratumumab-based quadruplet regimens. Adding daratumumab to traditional triplet regimens has demonstrated improved response rates and progression-free survival (PFS). However, the impact on long-term outcomes, particularly overall survival (OS), remains uncertain. This systematic review and meta-analysis aimed to compare the survival outcomes of these quadruplet regimens with triplets. Conducted in adherence to Cochrane Collaboration and PRISMA guidelines and registered on PROSPERO (CRD42024571946), the study involved searching PubMed, Embase, and Cochrane databases, from inception to June 2024. We included randomized clinical trials (RCT) and non-randomized controlled studies (NRCS) that compared daratumumab-based quadruplet regimens to triplets, focusing on OS and PFS, with a minimum follow-up of 18 months. The meta-analysis included 3327 TE-NDMM patients from four studies, comprising three RCT and one NRCS. Daratumumab-based regimens were administered to 1328 (40%) patients. The analysis revealed that daratumumab-based quadruplet regimens significantly improved both OS (pooled HR 0.60; 95% CI 0.48–0.75; P < 0.00001; I² = 0%) and PFS (pooled HR 0.49; 95% CI 0.37–0.65; P < 0.00001; I² = 52%). A per-protocol subgroup analysis comparing D-VRD to VRD further confirmed these benefits, with significant improvements in both OS (pooled HR 0.68; 95% CI 0.48–0.97; P = 0.03; I² = 0%) and PFS (pooled HR 0.41; 95% CI 0.31–0.54; P < 0.00001; I² = 0%). This meta-analysis consolidates evidence that daratumumab-based quadruplet regimens significantly improve OS, compared to triplet regimens for TE-NDMM patients.